Penyuluhan Pengelolaan Air Limbah Greywater Rumah Tangga dalam Upaya Meningkatkan Derajat Kesehatan Masyarakat - Maliga, Iga; Rafi'ah, Rafi'ah; Lestari, Ana; Pratama, Dicky Brian; Febriansyah, Diangga (Yayasan Literasi Sains Indonesia, 2022)
The use of clean water for daily and commercial needs will cause an increase in the amount of domestic waste. The increasing amount of domestic wastewater that is not matched by an increase in water bodies can cause problems related to surface water's carrying capacity and capacity. This community service aims to increase public awareness of the importance of domestic wastewater management, which can cause impacts on the environment and health. This service was carried out in Kukin Village, North Moyo District, in June 2021. The method of this community service activity was counseling on the importance of greywater wastewater management by involving 20 respondents who were visited door to door. The service showed that the community's understanding is still minimal regarding domestic wastewater management (greywater) in every home. This was indicated by the percentage of knowledge of the majority of respondents in the fewer categories as much as 65% and the remaining 35% in the good category. In addition, the majority of respondents initially let the greywater wastewater be thrown away as much as the remaining 50%, respectively 15% and 35%, were used for watering the yard and plants. The conclusion in this service is that the management of domestic liquid waste among the target community is still low. This activity can increase citizens' understanding to pay attention to wastewater from households and maintain public health.